Stitch in time saves nine: a retrospective study of uterine rupture over two years at a tertiary care hospital, Jabalpur - Patidar, Pragya; Mishra, Sakshi; Patel, Kirti; Singh, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Uterine rupture remains a critical obstetric emergency with unpredictable presentations and significant maternal-fetal risks. While often associated with prior caesarean sections, recent evidence points to a rising trend in unscarred ruptures in developing regions. This study aims to assess the incidence, risk profile, and outcomes of uterine rupture over a two-year period at a high-volume referral centre, identifying preventable gaps in care. Methods: A retrospective observational study was conducted at Netaji Subhash Chandra Bose Medical College, Jabalpur, from April 2022 to March 2024. All women with complete uterine rupture in the second or third trimester were included. Data on demographics, obstetric history, rupture site, surgical management, and maternal-fetal outcomes were analysed. Preventive factors such as antenatal care and referral delays were also examined. Results: Among 20,064 deliveries, 39 cases of uterine rupture were identified (1.94/1000). Of these, 61.5% occurred in scarred uteri and 38.5% in unscarred. Key contributing factors included short inter-delivery intervals, prolonged labour, previous uterine evacuation, and delayed referrals. Primary repair was performed in 71.8% of cases; hysterectomy and bladder repair were required in others. Maternal complications included anaemia, infection, and wound issues. The stillbirth rate was 74.4%, often linked to delayed presentation. Conclusions: In addition to known risk factors, poor spacing, unregulated uterotonic use, and systemic referral delays contribute significantly to uterine rupture. Strengthening antenatal counselling, timely referral mechanisms, and obstetric preparedness at peripheral levels is essential to reduce the burden of this preventable emergency.